Microbubble agents: new directions - Stride, E; Segers, T; Lajoinie, G; Cherkaoui, S; Bettinger, T; Versluis, M; Borden, M (Elsevier, 2020)
Microbubble ultrasound contrast agents have now been in use for several decades and their safety and efficacy in a wide range of diagnostic applications have been well established. Recent progress in imaging technology is facilitating exciting developments in techniques such as molecular, 3-D and super resolution imaging and new agents are now being developed to meet their specific requirements. In parallel, there have been significant advances in the therapeutic applications of microbubbles, with recent clinical trials demonstrating drug delivery across the blood–brain barrier and into solid tumours. New agents are similarly being tailored toward these applications, including nanoscale microbubble precursors offering superior circulation times and tissue penetration. The development of novel agents does, however, present several challenges, particularly regarding the regulatory framework. This article reviews the developments in agents for diagnostic, therapeutic and “theranostic” applications; novel manufacturing techniques; and the opportunities and challenges for their commercial and clinical translation.